Analyzing the Impact of Fintech and Banking Services on Shopee Usage: An Application of the Technology Acceptance Model (TAM) - Adelia Safitri; Nuri Aslami; Juliana Nasution (Indonesian Journal of Islamic Economics and Finance, 2026)
The development of digital technology has driven the transformation of payment systems and financial transactions, particularly through digital banking and financial technology (fintech) facilities, resulting in increased e-commerce usage. Drawing upon the Techonology Acceptance Model (TAM) as the theoretical foundation, this study aims to analyze the influence of banking and financial technology (fintech) facilities on Shopee e commerce usage among students of the Faculty of Islamic Economics and Business (FEBI) UIN North Sumatra class of 2022. This study used a quantitative method with a survey approach by distributing questionnaires to 91 respondents selected using a purposive sampling technique. Data were analyzed using multiple linear regression with the help of SPSS software, and validity, reliability, and classical assumption tests were conducted. The findings showed that partially banking and financial technology transaction facilities have a positive and significant influence on Shopee e-commerce usage. Simultaneously, both independent variables also have a significant influence on Shopee e-commerce usage. The coefficient of determination (Adjusted R Square) value of 0.968 indicates that 96.8% of the variation in Shopee e-commerce usage can be explained by banking and financial technology transaction facilities, while the remainder is influenced by other factors outside the study. The key finding reveals that fintech demonstrates a more dominant influence , reflecting higher perceived usefulness and ease of use through seamless platform integration, faster processing, and embedded incentives. The practical implication emphasize the need for banking institutions to enhance mobile banking UX/UI to match e-wallet flexibility, while universities should strengthen Islamic financial literacy programs addressing PayLater usage among students. The theoretical contribution extends the application of TAM in explaining digital payment adoption within Islamic economics contexts.